Factors affecting visual outcomes after treatment of infectious endophthalmitis in northeastern Thailand - Yospaiboon Y (Dove Medical Press, 2018)
Yosanan Yospaiboon, Anocha Intarapanich, Wipada Laovirojjanakul, Tanapat Ratanapakorn, Suthasinee Sinawat, Thuss Sanguansak, Chavakij Bhoomibunchoo KKU Eye Center, Department of Ophthalmology, Faculty of Medicine, Khon Kaen University, Khon Kaen, Thailand Objective: To determine factors affecting visual outcomes after treatment of infectious endophthalmitis during 2012–2016 at a large referral eye center in northeastern Thailand. Patients and methods: Medical charts of patients with a diagnosis of infectious endophthalmitis including demographic data, types of endophthalmitis, causative organisms, methods of treatment, anatomical, and functional outcomes were retrospectively reviewed. Factors associated with improved visual outcomes were analyzed.Results: Four hundred and eleven patients (417 eyes) were recruited for the study. The three most common types were post-traumatic (44.53%), post-operative (31.87%), and endogenous endophthalmitis (17.52%). Vitreous cultures revealed causative organisms in 41.25%. Most common Gram-positive organisms were coagulase-negative Staphylococcus 30% (36/120), Bacillus spp. 20% (24/120), and Streptococcus pneumoniae 18.33% (20/120). Most common Gram-negatives were Pseudomonas spp. 24.32% (9/37), Klebsiella spp. 24.32% (9/37), and Enterobacter spp. 16.21% (6/37). Methods of treatment were medical treatment (18.71%) and surgical treatment (81.29%), including pars plana vitrectomy with or without silicone oil tamponade (62.59%) and destructive surgery (18.71%). After treatment, visual improvement was noted in 44.6%, stable vision in 18.47%, and worse vision in 36.93%. Factors associated with improved visual outcomes were post-operative endophthalmitis (P<0.001), coagulase-negative Staphylococcus (P=0.003), and initial visual acuity before treatment of hand motion or better (P=0.017).Conclusion: Most infectious endophthalmitis patients were post-traumatic, post-operative, and endogenous. The most common method of treatment was pars plana vitrectomy. Treatment could improve visual outcomes and at least stabilize the vision in 63.07%. Factors associated with improved visual outcomes were types of endophthalmitis, causative organisms, and initial visual acuity before treatment. Keywords: visual outcome, infectious endophthalmitis, prognostic factors